First Nations Data Governance, Privacy, and the Importance of the OCAP® principles - Mecredy, Graham; Sutherland, Roseanne; Jones, Carmen (International Journal of Population Data Science, 2018)
Introduction Governance of First Nations data and information requires important considerations that go beyond those typically used in research. Researchers are generally not trained in how to work appropriately within the realm of First Nations data. Further, while Canadian legislation protects individual privacy, First Nations’ community privacy is not protected. Objectives and Approach The OCA® principles were created to fill these identified gaps. OCAP® is an acronym that outlines principles regarding the collection, use, and disclosure of data or information regarding First Nations. The letters in OCAP® describe four key principles: Ownership, Control, Access and Possession. Results First Nations OCAP® principles are beginning to make a paradigm shift in research. This shift in applying OCAP® is changing the standard for First Nations’ data and information. These principles give First Nations sovereignty over their data and information when applied appropriately. The principles go beyond the protection of individual privacy to include the additional consideration of community privacy, a vital issue when working with First Nations’ data. Conclusion/Implications OCAP®, when effectively applied, is a bridging tool for both First Nation communities and researchers to engage in relevant, reciprocal, and practical research projects to tell a story, provide insight, and effect policy change.